A Non-cognitive Behavioral Model for Interpreting Functional Neuroimaging Studies - Shulman, Robert G.; Rothman, Douglas L. (Frontiers in Human Neuroscience, 2019)
The dominant model for interpreting brain imaging experiments assumes that the brain is organized to support mental processes that control behavior. However functional neuroimaging experiments, particularly of cognitive tasks, have not shown a high level of reproducibility and localization. This lack of clear functional segregation has been blamed on limitations in imaging technology and non linearity and regional overlap in how the brain implements these processes. However the validity of the underlying cognitive models used to describe the brain have rarely been questioned or directly tested against imaging results. We propose an alternative model of brain function which correlates observed human behavior directly with measured brain activity without assumptions about intervening cognitive processes, that we term the Non-Cognitive Behavioral Model (NBM). Our model derives from Behavioral Psychology but is extended to include brain activations in addition to behavior as an observable. A further extension is the role of neuroplasticity as opposed to innate cognitive processes in the development of the brains support of cognitive behavior. Applications of NBM to neuroimaging studies are described and contrasted with the standard methodology which we refer to as the Standard Cognitive Model (SCM). In one application, the NBM correctly predicted the global, total energy consumption as the brain parameter that best correlates with a person being in the state of consciousness, a correlation missed by studies using the SCM due to its assumption that global activity does not support cognitive processes. Neuroplasticity is shown to provide a natural explanation of findings that object recognition activating the fusiform facial area comes from expertise through raining as opposed to the SCM explanation of an innate cognitive process specialized for face recognition. The conclusions are generalized to explain the poor reproducibility of cognitive processes reported in functional neuroimaging and to suggest how such studies can be used to better explain how the brain supports behavior.